Pengaruh Beban Kerja, Stres Kerja dan Kepuasan Kerja Terhadap Pendokumentasian Keperawatan di Ruang Rawat Inap Rumah Sakit Setukpa Polri Sukabumi - Abdul Rahman La Ede (Risenologi, 2022)
The implementation of the nursing care process uses an approach, namely with the Nursing Care Standard (SAK) which is a measuring tool to find out, monitor and assess the quality of nursing care that has been implemented by nurses, especially the methods, principles and strategies used by nurses in providing nursing care. Some of the factors that affect nursing documentation are workload, job stress and job satisfaction. The purpose of the study is to find out the influence of workload, work stress and job satisfaction on nursing documentation.This type of correlational research with a cross sectional approach. The population was 82 people and a sample of 73 respondents. Sampling techniques use Propotional Random Sampling. The instrument uses Nasa- TLX, DASS, MSQ and SAK RS. Data capture uses questionnaires and statistical analysis using simple linear regression and multiple linear regression. Bivariate analysis showed partial influence of workload on documenting of volunteers (p=0.000), work stress on nursing documentation (p=0.000), and job satisfaction on nursing documentation (p=0.000), and job satisfaction with nursing documentation (p=0.000). Multivariate results showed that there was a simultaneous influence of workload, work stress, and job satisfaction on nursing documentation (p=0.000). There is an influence of work stress, workload and job satisfaction on nursing documentation. It is hoped that the hospital can increase job satisfaction and reduce stress and workload to improve nursing documentation.